Identification and characterisation of the restorative hepatic macrophage - Ramachandran, Prakash (The University of Edinburgh, 2014)
Long thought to be irreversible, it is now clear that liver fibrogenesis is a dynamic process, with scar tissue capable of being remodelled as well as deposited. Macrophages have been shown to have a critical role in both liver fibrogenesis and fibrosis resolution. Whilst previous work has identified a Ly-6Chi hepatic macrophage population, derived from recruitment of inflammatory monocytes, as being the main pro-fibrogenic population, the nature and phenotype of the pro-resolution macrophage subset is unknown. In this thesis, I sought to identify and characterise this restorative hepatic macrophage. I established a reversible murine model of liver fibrosis using CCl4. At the time of initiation of fibrosis regression, Ly-6Clo CD11bhi F4/80int hepatic macrophages represented the most numerous macrophage population and the principal expresser of matrix degrading MMP enzymes. Depletion of this population in CD11b-diphtheria toxin (DTR) mice prevented fibrosis resolution. Subsequent, adoptive transfer and in situ labelling experiments, demonstrated that this restorative macrophage population derives from inflammatory monocytes, a common origin to the pro-fibrotic Ly-6Chi hepatic macrophage subset, indicating a switch in macrophage phenotype in situ to form the restorative phenotype. Characterisation of FACS-sorted restorative and pro-fibrogenic liver macrophage subsets using gene expression profiling demonstrated higher expression of pro-resolution genes and lower expression of pro-fibrotic genes in restorative macrophages, which also upregulated a number of genes involved in phagocytosis. Confocal microscopy confirmed that restorative macrophages showed evidence of prior phagocytosis. This could be replicated in vitro, where feeding macrophages with cellular debris resulted in matrix-degrading properties analogous to those seen in vivo, which was dependent on activation of the ERK signalling cascade. This effect was also demonstrated with the phagocytosis of liposomes in vitro. Finally, the administration of liposomes to CCl4-injured mice in vivo induced phagocytosis, causing an increase in hepatic restorative macrophage number and accelerating fibrosis regression. Hence, I have been able to identify and characterise the restorative hepatic macrophage and have utilised these data to develop a novel method to alter macrophage phenotype in vivo and accelerate the resolution of liver fibrosis and restoration of normal tissue architecture.
Keywords: liver fibrosis; macrophage